2021
DOI: 10.21037/atm-21-2590
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-preconditioned mesenchymal stem cells attenuate microglial pyroptosis after intracerebral hemorrhage

Abstract: Background: Microglia plays a vital role in neuroinflammation, contributing to the pathogenesis of intracerebral hemorrhage (ICH)-induced brain injury. Mesenchymal stem cells (MSCs) hold great potential for treating ICH. We previously revealed that MSCs ameliorate the microglial pyroptosis caused by an ischemic stroke. However, whether MSCs can modulate microglial pyroptosis after ICH remains unknown.This study aimed to investigate the neuroprotective effects of hypoxia-preconditioned olfactory mucosa MSCs (OM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 78 publications
(82 reference statements)
1
20
0
Order By: Relevance
“…NLRP3and caspase-1-positive cells were microglia, as determined through double immunofluorescence labeling. The authors also observed bubbles and large holes in the plasma membrane of microglia from the ICH group, in contrast to the linear and intact membrane from the sham-operated group, using a transmission electron microscope (Liu J. et al, 2021). Similar results were reported by Lin et al (2018), who demonstrated that NLRP3, caspase-1, and mature IL-1β expression were increased 24 h after ICH.…”
Section: Pyroptosissupporting
confidence: 78%
See 2 more Smart Citations
“…NLRP3and caspase-1-positive cells were microglia, as determined through double immunofluorescence labeling. The authors also observed bubbles and large holes in the plasma membrane of microglia from the ICH group, in contrast to the linear and intact membrane from the sham-operated group, using a transmission electron microscope (Liu J. et al, 2021). Similar results were reported by Lin et al (2018), who demonstrated that NLRP3, caspase-1, and mature IL-1β expression were increased 24 h after ICH.…”
Section: Pyroptosissupporting
confidence: 78%
“…NLR pyrin domain containing 3 (NLRP3) and NLRP1 inflammasome activate caspase-1 to initiate the cleavage and activation of interleukin-1β (IL-1β) and IL-18 leading to neuroinflammation and cell death after ICH (Bobinger et al, 2018; Figure 4). Liu J. et al (2021) found that the levels of NLRP3, cleaved caspase-1, cleaved caspase-8, and IL-1β were significantly increased 3 days post-ICH in mice. NLRP3and caspase-1-positive cells were microglia, as determined through double immunofluorescence labeling.…”
Section: Pyroptosismentioning
confidence: 91%
See 1 more Smart Citation
“…Recent studies have confirmed that MSCs are effective modifiers maintaining a resting microglial phenotype, preventing microglial activation by downregulating pro-inflammatory cytokines/chemokines and upregulating hypoxia-inducible factor 1-alpha (HIF-1α) and growth factors including VEGF, BDNF, GDNF, stromal-derived factor-1 (SDF-1), and erythropoietin (EPO) following stroke ( Wei et al, 2012 ; Yan et al, 2013 ). Other studies have shown that hypoxic preconditioning augmented MSC survival and tissue-protective capability, displaying better therapeutic efficacy than the single MSC transplantation by improving the miR-326/PTBP1/PI3K-mediated autophagy and alleviated microglial activation to downregulate IL-1β and TNF-α expression levels and microglial pyroptosis after ICH ( Liu et al, 2021a , b ). Human ADMSCs improved the neurological deficits in the ICH mice model by suppressing the acute inflammation mediated by the CD11 + CD45 + subpopulation of cells ( Kuramoto et al, 2019 ).…”
Section: Mechanisms Of Mesenchymal Stem Cells In Intracerebral Hemorr...mentioning
confidence: 99%
“…Probably, hypoxic preconditioning led to the reduction in microglial pyroptosis through a mechanism mediated by NLRP3 inflammasome to promote the passage of microglia into the anti-inflammatory phenotype. Moreover, mice transplanted with preconditioned OM-MSCs showed an improvement in behavioral deficits [69].…”
Section: Mscs Preconditioning With Hypoxia In In Vitro Studiesmentioning
confidence: 99%